The Relationship Between Cyberbullying and Suicidal Ideation in Adolescent Girls The Mediating Role of Perceived Maternal Acceptance and Perceived Burdensomeness - Naghash Souratgar, Kiana; Aziziani Khoshnami, Hadis; Haidari Nia, Mehran (Journal of Assessment and Research in Applied Counseling (JARAC), 2026)
Objective: The present study aimed to investigate the relationship between cyberbullying and suicidal ideation among adolescent girls and to examine the mediating roles of perceived maternal acceptance and perceived burdensomeness in this relationship. Methods and Materials: This study employed a descriptive-correlational design using structural equation modeling (SEM). The statistical population consisted of female high school students in Qazvin, Iran, during the 2025–2026 academic year. Using a multistage cluster sampling method, 520 students were recruited, of whom 498 valid questionnaires were retained for analysis. Data were collected using the Cyberbullying Scale (CBS), the Beck Scale for Suicide Ideation (BSSI), the Perceived Burdensomeness subscale of the Interpersonal Needs Questionnaire (INQ), and the Perceived Maternal Acceptance Scale (PMAS). Descriptive statistics, Pearson correlation coefficients, and structural equation modeling were performed using SPSS version 28 and AMOS version 24. The significance of indirect effects was assessed through bootstrap analysis with 5,000 resamples and 95% confidence intervals. Findings: The results revealed significant positive correlations between cyberbullying and suicidal ideation (r = .48, p < .01) and between cyberbullying and perceived burdensomeness (r = .42, p < .01). Cyberbullying was negatively associated with perceived maternal acceptance (r = -.39, p < .01). Structural equation modeling demonstrated satisfactory model fit (χ²/df = 2.29, CFI = .95, TLI = .94, RMSEA = .051). Cyberbullying had significant direct effects on perceived burdensomeness (β = .45, p < .001), perceived maternal acceptance (β = -.41, p < .001), and suicidal ideation (β = .19, p < .001). Perceived burdensomeness positively predicted suicidal ideation (β = .47, p < .001), whereas perceived maternal acceptance negatively predicted suicidal ideation (β = -.34, p < .001). Bootstrap analyses confirmed significant indirect effects through perceived burdensomeness (Effect = .21, 95% CI [.14, .29]) and perceived maternal acceptance (Effect = .14, 95% CI [.08, .21]). Conclusion: The findings indicate that cyberbullying is a significant predictor of suicidal ideation among adolescent girls. Perceived burdensomeness and perceived maternal acceptance partially mediate this relationship, suggesting that both interpersonal cognitive vulnerabilities and family-based protective factors play crucial roles in understanding adolescent suicide risk. Interventions aimed at reducing cyberbullying, strengthening maternal acceptance, and addressing maladaptive perceptions of burdensomeness may contribute to the prevention of suicidal ideation in adolescents.